Analysis of Apical Root Transportation Associated with Protaper Universal F3 and F4 Instruments by Using Digital Subtraction Radiography - Kunert, Gustavo Golgo; Camargo Fontanella, Vania Regina; Maranhao de Moura, Abilio Albuquerque [UNESP]; Barletta, Fernando Branco (Elsevier B.V., 2010)
Introduction: The aim of this study was to assess the occurrence of apical root transportation after the use of Pro Taper Universal rotary files sizes 3 (F3) and 4 (F4). Methods: Instruments were worked to the apex of the original canal, always by the same operator. Digital subtraction radiography images were produced in buccolingual and mesiodistal projections. A total of 25 radiographs were taken from root canals of human maxillary first molars with curvatures varying from 23-31 degrees. Quantitative data were analyzed by intraclass correlation coefficient and Wilcoxon nonparametric test (P = .05). Results: Buccolingual images revealed a significantly higher degree of apical transportation associated with F4 instruments when compared with F3 instruments in relation to the original canal (Wilcoxon test, P = .007). No significant difference was observed in mesiodistal images (P = .492). Conclusions: F3 instruments should be used with care in curved canals, and F4 instruments should be avoided in apical third preparation of curved canals. (J Endod 2010;36:1052-1055)
Keywords: Digital radiography; endodontics; instrumentation; root canal preparation; root transportation